2014
DOI: 10.1002/chem.201405155
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Copper(I) Complexes that Exhibit Monooxygenase and Catechol Dioxygenase Activity

Abstract: New tripodal ligand L2 featuring three different pyridyl/imidazolyl-based N-donor units at a bridgehead C atom, from which one of the imidazolyl units is separated by a phenylene linker, was synthesized and investigated with regards to copper(I) complexation. The resulting complex [(L2)Cu]OTf (2(OTf)), the known complex [(L1)Cu]OTf (1(OTf); L1 differs from L2 in that it lacks the phenylene spacer) and [(L3)Cu]OTf (3(OTf)), prepared from a known chiral, tripodal, N-donor ligand featuring pyridyl, pyrazolyl, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Those species were also capable of oxygen activation. Earlier this year, they demonstrated the hydroxylation of 2,4‐di‐ tert‐ butylphenol (DTBP) to the corresponding quinone with this system 42. In parallel, Stack et al.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Those species were also capable of oxygen activation. Earlier this year, they demonstrated the hydroxylation of 2,4‐di‐ tert‐ butylphenol (DTBP) to the corresponding quinone with this system 42. In parallel, Stack et al.…”
Section: Introductionmentioning
confidence: 96%
“…Earliert his year,t hey demonstrated the hydroxylationo f2 ,4-ditert-butylphenol( DTBP)t ot he corresponding quinonew itht his system. [42] In parallel,S tack et al showed that a P species with simplem ethylimidazoles could be stabilised at extremely low temperatures of À120 8Ca nd also displayed hydroxylationa ctivity. [43] Remarkably,t hese previous imidazolyl-containing systems did not show the catalytic activity demonstrated herein with the novel bis(pyrazolyl)imidazolylmethane ligand HC(3-tBuPz) 2 (1-MeIm) (L).…”
Section: Introductionmentioning
confidence: 99%
“…Bio-oxidation reactions have inspired the design of a library of metal complexes, which led to many successful functional models of enzymes over the past few decades [1][2][3][4][5]. These complexes have gained importance for their ability to shed insight on the mechanistic pathways of the original enzymes.…”
Section: Introductionmentioning
confidence: 99%